Reputation and Competition - Höner, Johannes (American Economic Review, 2002)
This paper shows how competition generates reputation-building behavior in repeated interactions when the product quality observed by consumers is a noisy signal of firms' effort level. There are two types of firms and “good” firms try to distinguish themselves from “bad” firms. Although consumers get convinced that firms which are repeatedly successful in providing high quality are good firms, competition endogenously generates the outside option inducing disappointed consumers to leave firms. This threat of exit induces good firms to choose high effort, allowing good reputations to be valuable, but its uncompromising execution forces good firms out of the market.